Визначення поняття неповнолітнього підозрюваного у кримінальному провадженні - Пієв, С. С.; Piev, S. S. (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 2 (69). - С. 109-116., 2015)
Розглянуто положення міжнародно-правових актів та національного законодавства з питань регламентації кримінального провадження щодо неповнолітніх. Окремо досліджено питання щодо визначення віку, з якого настає кримінальна відповідальність, відповідно до законодавства України та деяких інших країн. Запропоновано періодизацію віку неповнолітньої особи залежно від можливості вчинення нею нетяжкого суспільно небезпечного діяння та залучення її у зв’язку з цим до кримінального судочинства. Сформульовано поняття неповнолітнього підозрюваного.

It is proved that the concept of the age of a minor suspect that is contained in the current Criminal Procedural Code of Ukraine is imperfect. In order to improve this concept a comparison of international and legal acts is conducted; and it is found out that different countries at the legislative level have polar definitions of the studied concept, and the age of bringing minors to criminal liability in criminal proceedingsvaries from 7 to 18 years. National legislation concerning the term of «a minor» is studied. The regulation of criminal proceedings, where the participants are minor suspects and accused persons is analyzed; at the same time certain gaps and inconsistencies are established. Academic positions of scholars concerning studied issues are provided; the lack of clarity and consensus in defining the studied concept is found out. After singling out one of the most spread positions of scholars about the furtherestablishment of a reduced age of criminal liability for juveniles, who in the present state are more informed about crime and social behavior and their personal estimation, the author has grounded his own scientific position about the fallacy of such approaches. It is emphasized on the need to continue the implementation of international tendencies of developing juvenile justice in Ukraine, according to the provisions of which the offence committed by a minor may be provided with the legal assessment beyond the criminal proceedings and judicial proceedings, if a particularly serious crime is not committed. Before taking such a decision in Ukraine, periodization and classification of the age of a minor, depending on the possibility to commit not serious, socially dangerous act (omission) and involvement in regard to this to the criminal proceedings and judicial proceedings under the current legislation, are offered. By the results of the study the author’s concept of a minor suspect is formulated.

Рассмотрены положения международно-правовых актов и национального законодательства по вопросам регламентации уголовного производства в отношении несовершеннолетних. Отдельно исследованы вопросы определения возраста, с которого наступает уголовная ответственность, в соответствии с законодательством Украины и некоторых других стран. Предложена периодизация возраста несовершеннолетнего в зависимости от возможности совершения им общественно опасного деяния и вовлечения его в связи с этим в уголовное судопроизводство. Сформулировано понятие несовершеннолетнего подозреваемого.
Piev, S.S. (2015), “Determining the concept of a minor suspect within criminal proceedings”, [“Vyznachennia poniattia nepovnolitnoho pidozriuvanoho u kryminalnomu provadzhenni”], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 109-116.
Пієв, С. С. Визначення поняття неповнолітнього підозрюваного у кримінальному провадженні // Вісник Харківського національного університету внутрішніх справ. - 2015. - № 2 (69). - С. 109-116.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; міжнародно-правові акти; КПК України; кримінальне провадження щодо неповнолітніх; досудове розслідування; неповнолітній підозрюваний; вік особи; законний представник; захист неповнолітньої особи; international and legal acts; Criminal Procedural Code of Ukraine; criminal proceedings against minors; pre-trial investigation; minor suspect; person’s age; legal representative; defense of a minor; международно-правовые акты; УПК Украины; уголовное производство в отношении несовершеннолетних; досудебное расследование; несовершеннолетний подозреваемый; возраст лица; законный представитель; защита несовершеннолетнего; Кримінальний процесуальний кодекс України